Mechanical drafter - Wallner, Rosemary (Mankato, Minnesota : Capstone Press, 2000)
Introduces the career of mechanical drafter, discussing educational requirements, duties, work environment, salary, employment outlook, and possible future positions.
Includes bibliographical references and index.
Keywords: Mechanical drawing -- Vocational guidance -- Juvenile literature; Drafters -- Vocational guidance -- Juvenile literature